Quantifying the effect of carbohydrate mouth rinsing on exercise performance - Peart, D. J. (The Journal of Strength and Conditioning Research, 2017)
The purpose of this study was to review the existing literature investigating carbohydrate mouth rinsing as an ergogenic aid using the effect sizes (ES) and percentage change in performance of the respective studies as outcome measures. A trivial-small average overall ES was present for the 25 studies included in the review (0.18, 95% confidence interval [CI] = 0.10-0.27). Effect sizes for the subgroups were =25 minutes (0.25, 95% CI = 0.14-0.36), =180 seconds (0.06, 95% CI = -0.03 to 0.15), resistance exercise (-0.09, 95% CI = -0.20 to 0.03) but the ES is still small. A subanalysis of ~1-h cycling time trial performance resulted in an overall ES of 0.20 (95% CI = 0.02-0.38), and ES for performance time and power output of 0.31 (95% CI = -0.02 to 0.64) and 0.19 (95% CI = -0.09 to 0.46), respectively. Although ES were small, the average percentage change in performance in ~1-hour trials was 2.48%, which may have implications for elite performers as this is greater than the 1.30% smallest worthwhile change recommended in the past research.